Muslimah Intention on Halal Cosmetic: A SEM PLS - Nurhidayati Bintu Jalil (SMART Insight, 2022)
Since the last 5 years the halal industry has now captured a lot of public attention, not only from the food sector but also extends to the tourism, hospitality, pharmaceutical and cosmetic sectors. The increasing demand for Muslim consumers for halal products is a business opportunity for producers or companies. The growth of the cosmetics market is projected to increase by 7% in 2021. This study aims to determine the buying intention of Muslims in buying or using halal cosmetics using the Theory of Planned Behavior (TPB). Data was collected by distributing questionnaires online. Then the collected data was processed using Structural Equation Modeling-Partial Least Square (SEM-PLS) and concluded that it is known that the latent variable attitude has a path coefficient value of 0.026, this shows a positive influence on purchase intentions.